The Use of Various Forms in Teaching Future Primary School Teachers Through Distance Learning (Eurasian Journal of Humanities and Social Sciences, 2022)
The importance, forms and types of distance learning are given in this article. The article covers lectures, practical training, their content, achievements and disadvantages in the traditional and distance learning process. The effectiveness of the application of distance learning in the educational process has been given.